The advancement of technology and the concept of distance learning in the global context: Reaching out the unreachable - Kuboja, Joshua; Mwakobela, Upendo (Papanda Publisher, 2024)
The field of education has changed significantly due to the rapid progress of technology, especially in the area of online learning. This paper examines how technology has enabled education to reach new populations worldwide, expanding access to learning opportunities. By examining present trends and advancements in distance learning technologies, this paper explains how technology has connected geographical, socio-economic, and cultural obstacles to education. It explores how digital platforms, virtual classrooms, online resources, and interactive learning tools can increase access to quality education and empower people regardless of where they are from or their background. Moreover, this study explores the difficulties and advantages linked with the worldwide adoption of remote learning projects. It explores topics like the digital divide, limitations in infrastructure, adjustments in teaching methods, and understanding different cultures, while also showcasing creative solutions and successful strategies used to tackle these obstacles. Using information from academic sources, real-life examples, and research studies, this paper enhances our comprehension of how technology-based remote learning is changing the global educational scenery. It highlights how using technology can help connect with those who are typically out of reach, promoting equal access to education for everyone.